2017
DOI: 10.1159/000485650
|View full text |Cite
|
Sign up to set email alerts
|

MiR-106b-5p Promotes Proliferation and Inhibits Apoptosis by Regulating BTG3 in Non-Small Cell Lung Cancer

Abstract: Background/Aims: MicroRNAs have been validated to play a crucial role in tumorigenesis of non-small cell lung cancer (NSCLC). Although miR-106b-5p has been reported to play a vital role in various malignancies the physiological function of miR-106b-5p in NSCLC still remain unknown. In this study, we investigated the role of miR-106b-5p in NSCLC. Methods: Quantitative real-time polymerase chain reaction was conducted to estimate the expression of miR-106b-5p and BTG3 in both NSCLC tissues and cell lines. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 51 publications
1
45
1
Order By: Relevance
“…A previous study has shown that microRNAs are involved in multiple aspects of lung cancer such as cell proliferation, apoptosis, invasion, and EMT (3)(4)(5)(6). Additionally, the survival of lung cancer patients has been predicted by a series of microRNAs such as miR-133b, miR-93-5p (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that microRNAs are involved in multiple aspects of lung cancer such as cell proliferation, apoptosis, invasion, and EMT (3)(4)(5)(6). Additionally, the survival of lung cancer patients has been predicted by a series of microRNAs such as miR-133b, miR-93-5p (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…A number of miR-106b-5p target genes have been identified, including SET domain containing 2, histone lysine methyltransferase (11), cathepsin A (27), PTEN (14) and BTG anti-proliferation factor 3 (15), which have pivotal roles in anti-oncogenic processes. Since miRNAs depress the expression of their target mRNAs, the present study hypothesized that miR-106b-5p may target certain genes that function as tumor suppressors.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs cause mRNA degradation and post-transcriptional downregulation by binding to the 3'untranslated region (UTR) of their target genes (10). miR-106b-5p, a member of the miR-106b-25 cluster, is mapped to human chromosome 7q21 (Chr7q21) locus and has been reported to be amplified in several types of human malignancies, including renal cell carcinoma (11), hepatocellular carcinoma (12), glioma (13), melanoma (14) and non-small cell lung cancer (15). The deleterious effects of miRNA dysregulation on malignant behaviors appear to be strongly associated with tumorigenesis and cell cycle progression (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the underlying mechanism by which NSCLC is modulated is not fully understood (25). miRNAs are key regulators of NSCLC progression and therefore may become an important therapeutic target (26). The abnormal expression of circulating miRNA has also been widely reported in patients with NSCLC (6,26).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are key regulators of NSCLC progression and therefore may become an important therapeutic target (26). The abnormal expression of circulating miRNA has also been widely reported in patients with NSCLC (6,26). Increasing evidence has indicate the important role of miR-484 in various types of tumor (18,27,28).…”
Section: Discussionmentioning
confidence: 99%